Conjugate radiation-convection-conduction simulation of volumetric solar receivers with cut-back inlets. (August 2018) - Nakakura, Mitsuho; Bellan, Selvan; Matsubara, Koji; Kodama, Tatsuya
Highlights: Conjugate analysis was made for volumetric receivers by DO radiation computation. The cut-back receivers increased the exit temperature and decreased pressure loss. Attenuation of shadow effects caused preferable performance of cut-back receivers. Abstract: This study analyzes the effect of cut-back inlets on the conjugate heat transfer of honeycomb-channel solar receivers. Two-way coupling simulations are reported for a plane-surface inlet, and five kinds of cut-back inlet receivers. The receivers are based on a 1.9-mm × 1.9-mm square cell with a 1.0-mm wall thickness. The cut-back inlet receivers have different amounts of material removed from the walls at the channel inlets. Numerical simulations demonstrate that receivers with a 2.4-mm cut from the channel inlet increased the exit temperature by 20.0 K or more, and decreased the pressure drop relative to the plane-surface receiver. Therefore, the results indicate that the cut-back inlet receiver's thermal, and hydrodynamic performance is better for industrial use than is the plane-surface receiver. This performance is then explained with detailed examinations of the individual heat-transfer processes in the model. These detailed comparisons indicate that the top cuts reduce shadow effects as light irradiates the channel walls, allowing more direct irradiation to reach the wall surface, thus improving the overall performance.